The relationship between macroeconomic with housing price index / Marina Zukifli - Zukifli, Marina (Faculty of Business Management, 2017)
The objectives of this study to investigate the relationship between two variable which are dependent variable and independent variable. From this study, there were three macroeconomic variable namely interest rate, inflation rate, and growth domestic product. All this variable will call as independent variable. The dependent variable is housing price index. This research is the relationship between macroeconomic with housing price index variables from 2005 until 2014 by using quarterly month. This research use Multiple Regression in order to examine the relationship between macroeconomic with housing price index variables. The data was analysed by using time-series data and this project paper had been tested for several statistics. These findings have proven that these three of independent variables are significant with dependent variable.